Perovskite absorption layer and preparation method thereof, and polyionic liquid-ionic liquid synergistically modified perovskite solar cell

By using polyionic liquids and ionic liquid synergistic additives in perovskite solar cells, a high-quality perovskite absorber layer was prepared, solving the problems of pore control and interface effects in perovskite thin-film batteries, improving the uniformity and efficiency of the cells, and making it suitable for flexible photovoltaic devices and commercial production.

CN121099882APending Publication Date: 2025-12-09INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1

Patent Information

Application Number
CN202511138915.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing perovskite thin-film solar cells suffer from problems such as difficulty in controlling pore size, film inhomogeneity, insufficient filling and localized stacking, interface effects, and excessively rapid perovskite crystallization, resulting in poor repeatability, low efficiency, and insufficient stability.

Method used

By synergistically adding polyionic liquid and ionic liquid to perovskite solar cells, and by optimizing the perovskite precursor solution, spin-coating and annealing are performed to form a high-quality perovskite absorber layer, thereby achieving dual passivation of bulk and interface defects.

Benefits of technology

It improves thin film uniformity and photoelectric efficiency, solves the balance problem of efficiency, stability and large-area fabrication of perovskite cells, and is suitable for the production of flexible photovoltaic devices and commercial modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121099882A_ABST
    Figure CN121099882A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite absorption layer and a preparation method thereof, and a polyion liquid-ion liquid synergistically modified perovskite solar cell, belongs to the technical field of solar cells, and aims to solve the problems of bulk phase and interface defects of the perovskite solar cell. The preparation method of the perovskite absorption layer comprises the following steps: dispersing and dissolving a perovskite precursor, polyionic liquid and ionic liquid into an organic solvent to prepare a perovskite precursor solution; and spin-coating the perovskite precursor solution to form a film, and annealing to obtain the perovskite absorption layer. According to the invention, polyionic liquid (PIL) and ionic liquid (IL) are preferably and synergistically added into a single-junction or multi-junction photovoltaic cell containing perovskite junctions, so that dual passivation of bulk phase and interface defects is realized; and the film uniformity and the photoelectric efficiency are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of solar cells, and particularly relates to a perovskite solar cell. Background Technology

[0002] In the field of solar cells, improving photoelectric conversion efficiency and reducing costs have always been the core goals of research and development. Currently, while perovskite thin-film solar cells have achieved some success, their technological development still faces many bottlenecks. Existing perovskite thin-film solar cell device structures mainly include mesoporous and planar structures. In mesoporous structures, the sol-gel method is a commonly used method for synthesizing mesoporous materials; however, preparation conditions such as temperature, concentration, processing time, and crystal form significantly affect pore size. This leads to limited crystal growth of metal halide perovskite materials filling the mesoporous support layer, resulting in problems such as uncontrollable pores, uneven film, insufficient filling, and severe local accumulation, leading to significant differences in the repeatability of devices with the same structure. Planar heterojunction perovskite solar cell structures are affected by interface effects and surface tension during perovskite crystallization. Excessive perovskite film crystallization speed results in poor film formation, leading to increased porosity and surface roughness in the perovskite layer. Subsequently deposited hole transport layers or electron transport layers may directly contact the dense layer through these pores, thereby increasing leakage current. These problems severely restrict the further development of perovskite thin-film battery technology. The growth process of perovskite crystals is complex and influenced by various parameters of the reaction system, such as temperature, solution, solvent, and additives. Even small changes in these parameters can lead to lattice distortion, significantly affecting the energy band structure of the perovskite material and consequently impacting the injection and transport of charge carriers at the interface. Therefore, preparing high-quality perovskite crystal films with low defect states is crucial for obtaining high-efficiency perovskite solar cell devices. Existing research utilizes additives such as DMSO, DIO, chlorinated compounds, and chloronaphthalene. Furthermore, ionic liquids are frequently used to passivate perovskite defects. Imidazole-based ionic liquids (such as 1-methyl-3-aminopropylimidazolium hexafluorophosphate) passivate lead defects through coordination, improving efficiency. Ionic liquids containing sulfur heterocycles or sulfonic acid groups enhance bonding with lead ions in the perovskite and inhibit ion migration. For example, patent publication number CN 106816535A discloses a method for improving the efficiency of perovskite solar cells using ionic liquid additives. The process is as follows: (1) Preparation of precursor mixed solution: lead acetate and methyl iodide are dissolved in N,N-dimethylformamide solution to form a mixed solution; 1-ethylpyridine chloride ionic liquid is added as an additive to prepare a precursor mixed solution; (2) Preparation of perovskite thin film: the precursor mixed solution is spin-coated onto a conductive glass substrate with PEDOT:PSS, and annealed on a hot stage to obtain a perovskite thin film; (3) Deposition of electron transport layer: the electron transport layer is deposited on the perovskite thin film by hot evaporation or solution spin coating; (4) Evaporation of counter electrode: a metal aluminum electrode is vapor-deposited by vacuum deposition. For example, patent publication number CN 114242902 A describes a method for improving the air stability of an inverse all-inorganic perovskite solar cell based on ionic liquid. The structure, from bottom to top, consists of an ITO layer, a hole transport layer, a perovskite absorber layer, an ionic liquid layer, an electron transport layer, a buffer layer, and a metal electrode. The perovskite precursor solution contains an imidazole-based ionic liquid. While adding the ionic liquid modulates the perovskite crystal growth kinetics to some extent and improves the quality of the crystal film, it does not fundamentally solve the problems of bulk and interface defects. Summary of the Invention

[0003] To address the aforementioned technical problems, this invention proposes a perovskite absorber layer and its preparation method, as well as a perovskite solar cell synergistically modified with polyionic liquid-ionic liquid. By synergistically adding polyionic liquid (PIL) and ionic liquid (IL) to the perovskite cell, dual passivation of bulk and interface defects is achieved, thereby improving film uniformity and photoelectric efficiency.

[0004] To achieve the above objectives, the technical solution of the present invention is implemented as follows: A method for preparing a perovskite absorber layer involves dissolving a perovskite precursor, a polyionic liquid, and an ionic liquid in an organic solvent to prepare a perovskite precursor solution; spin-coating the perovskite precursor solution into a film; and annealing to obtain the perovskite absorber layer. The perovskite absorber layer is used in the preparation of single-junction or multi-junction photovoltaic cells containing a perovskite active layer, such as two-terminal / four-terminal all-perovskite tandem cells, organic-perovskite tandem cells, perovskite-silicon tandem cells, and perovskite-CIGS tandem cells.

[0005] Preferably, a perovskite solar cell modified with polyionic liquid-ionic liquid synergistically has a structure consisting of a bottom electrode layer, a hole transport layer, a perovskite absorber layer, an electron transport layer, and a top electrode layer from bottom to top.

[0006] The perovskite precursor is a raw material for forming the ABX3 perovskite structure, wherein A is an organic cation and / or a Group 1 metal cation, such as methylamine cation (MA). + The source is methylamine hydroiodate (MAI, CH3NH3I), formamidin cation (FA). + The source is formamidinium hydroiodate (FAI, HC(NH2)2I), cesium ion (Cs) + ): The source is CsI or CsBr; B is one or more of Pb, Sn, Bi, Cu and Ag; X is one or more of Cl, Br and I.

[0007] Preferably, lead ions (Pb) 2+ The source is PbI2, PbBr2 or PbCl2, tin ions (Sn) 2+ ): The source is SnI2.

[0008] Preferably, bromide ions (Br) - ): Sources include PbBr2, MABr, etc.; iodide ions (I - Sources include MAI, FAI, PbI2, etc.; chloride ions (Cl...) - ): Sources include PbCl2, MACl, etc.

[0009] Preferably, the perovskite precursor may also contain additives (to regulate crystallization and stability). For example, formamide (FA) reduces the viscosity of the precursor solution, promotes perovskite crystallization, and reduces defects; a small amount of cesium chloride (CsCl) can inhibit perovskite grain growth and improve film uniformity; lithium iodide (LiI) improves hole transport performance and reduces interfacial recombination.

[0010] Preferably, the perovskite precursor includes CsI, MAI, FAI, PbI2, SnI2, MACl, and MABr, etc.

[0011] The concentrations of each component raw material in the perovskite precursor solution are conventionally selected in the art, for example, the molar ratio of A / B / X is 1:1:3.

[0012] The general structural formula of the polyionic liquid is [R1R2A]. + -R3] n [X - ] n Where R1 and R2 are independently selected from C1-C 18 Alkyl, alkenyl, aryl, or polymeric chain; R3 is H or C1-C5 alkyl; X- is selected from Cl - ,Br - I - [BF4] - [PF5] - [SCN] - [Tf2N] - Or [CH3COO] - A represents imidazole or pyridine; the degree of polymerization n is 5-1000.

[0013] The general formula of the ionic liquid structure is [R1R2A]. + -R3][X - ], where R1 and R2 are independently selected from C1-C 18 Alkyl, alkenyl, aryl, or polymeric chain; R3 is H or C1-C5 alkyl; X- is selected from Cl - ,Br - I - [BF4] - [PF5] - [SCN] - [Tf2N] - Or [CH3COO] - A represents imidazole or pyridine.

[0014] Preferably, the polyionic liquid is polyvinyl-3-butylimidazolium chloride; the ionic liquid is 1-butyl-3-methylimidazolium thiocyanate.

[0015] The organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, 2-methoxyethanol, and methyl acetate.

[0016] The concentration of the polyionic liquid in the perovskite precursor solution is 0.1-10 mg / ml, and the concentration of the ionic liquid is 0.1-10 mg / ml.

[0017] The annealing temperature is 50-250℃, and the time is 5-60 minutes.

[0018] Preferably, the concentration of the polyionic liquid in the perovskite precursor solution is 1 mg / ml, and the concentration of the ionic liquid is 0.5 mg / ml.

[0019] Preferably, the annealing temperature is 120°C and the time is 10 minutes.

[0020] The beneficial effects of this invention are: (1) This invention anchors perovskite grain boundaries through a long-chain polymer network (PIL) to suppress ion migration, while simultaneously using IL to fill grain boundary voids, passivating uncoordinated iodine ions on the surface and reducing interfacial energy level mismatch. The synergistic passivation mechanism of these two mechanisms achieves dual passivation of bulk and interfacial defects, improving film uniformity and photoelectric efficiency.

[0021] (2) This invention solves the balance problem of efficiency, stability and large-area fabrication of perovskite solar cells through material design and process innovation, and is especially suitable for flexible photovoltaic devices and commercial module production. Experimental data show that its overall performance is better than that of a single passivating agent system. Attached Figure Description

[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0023] Figure 1 This is a schematic diagram of a perovskite solar cell structure.

[0024] Figure 2 The current density-voltage curve of the perovskite solar cell prepared for Comparative Example 1 is shown.

[0025] Figure 3 The current density-voltage curve of the perovskite solar cell prepared for Comparative Example 2 is shown.

[0026] Figure 4 The current density-voltage curve of the perovskite solar cell prepared for Comparative Example 3 is shown.

[0027] Figure 5 The current density-voltage curve of the perovskite solar cell prepared in Example 1 is shown.

[0028] Figure 6 The current density-voltage curve of the perovskite solar cell prepared in Example 2 is shown.

[0029] Figure 7 The current density-voltage curve of the perovskite solar cell prepared in Example 3 is shown.

[0030] Figure 8 This is a depth profile of the elements in the perovskite solar cell device prepared in Example 1.

[0031] Figure 9 The dark current density-voltage characteristic curves of pure hole devices are shown for the solar cells corresponding to Example 1, Comparative Examples 1, 2 and 3.

[0032] Figure 10 The storage stability of the solar cells corresponding to Example 1, Comparative Examples 1, 2 and 3 in an N2 atmosphere. Detailed Implementation

[0033] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of them. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Hole transport layer, perovskite absorber layer, electron transport layer, and metal electrode. Example 1 A perovskite solar cell synergistically modified with polyionic liquid and ionic liquid, with the structure as follows: Figure 1 As shown, the structure of this battery includes: a glass substrate, a bottom electrode layer (FTO conductive glass), a hole transport layer (hybrid SAMs), and a perovskite absorber layer (Cs). 0.05 MA 0.1 FA 0.85 PbI3), electron transport layer (C60, BCP), top electrode layer (silver electrode).

[0034] The perovskite solar cell is prepared as follows: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0035] Preparation of perovskite precursor solution: Add 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI2 to 0.9 mL of a mixed dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solution (745 μL DMF + 155 μL DMSO). Then add 15 mg MACl and 35 mg PbI2 to improve the quality of the perovskite film. Add PIL-1 (P[bvim]Cl) (1 mg / mL) and IL ([bmin]SCN) (0.5 mg / mL) and stir to form a homogeneous solution.

[0036] Spin-coating: The mixed SAMs solution was spin-coated onto FTO at 3000 rpm for 30 s, and then annealed at 120 °C for 10 min. The perovskite precursor solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Then, it was annealed at 120 °C for 10 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, and then annealed at 100 °C for 5 min.

[0037] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0038] Example 2 A perovskite solar cell synergistically modified with polyionic liquid and ionic liquid is prepared by the following method: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0039] Preparation of perovskite precursor solution: Add 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI2 to 0.9 mL of a mixed dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solution (745 μL DMF + 155 μL DMSO). Then add 15 mg MACl and 35 mg PbI2 to improve the quality of the perovskite film. Add PIL-2 (P[bvim]SCN) (concentration 1 mg / mL) and IL ([bmin]SCN) (concentration 0.5 mg / mL) and stir to form a homogeneous solution.

[0040] Spin-coating: The mixed SAMs solution was spin-coated onto FTO at 3000 rpm for 30 s, and then annealed at 120 °C for 10 min. The perovskite precursor solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Then, it was annealed at 120 °C for 10 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, and then annealed at 100 °C for 5 min.

[0041] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0042] Example 3 A perovskite solar cell synergistically modified with polyionic liquid and ionic liquid is prepared by the following method: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0043] Preparation of perovskite precursor solution: 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI2 were added to 0.9 mL of a mixed dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solution (745 μL DMF + 155 μL DMSO). Then, 15 mg MACl and 35 mg PbI2 were added to improve the quality of the perovskite film. PIL-3 (P[bvim]PF6) (1 mg / mL) and IL ([bmin]SCN) (0.5 mg / mL) were added, and the mixture was stirred to form a homogeneous solution.

[0044] Spin-coating: The mixed SAMs solution was spin-coated onto FTO at 3000 rpm for 30 s, and then annealed at 120 °C for 10 min. The perovskite precursor solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Then, it was annealed at 120 °C for 10 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, and then annealed at 100 °C for 5 min.

[0045] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0046] Comparative Example 1 A perovskite solar cell is fabricated as follows: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0047] Precursor solution preparation: Add 0.075 mmol of CsI, 0.15 mmol of MAI, 1.275 mmol of FAI and 1.5 mmol of PbI2 to 0.9 mL of a mixed solution of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (745 μL DMF + 155 μL DMSO), and then add 15 mg of MACl and 35 mg of PbI2 to improve the quality of the perovskite film.

[0048] Spin-coating: SAM in ethanol solution was spin-coated onto FTO at 3000 rpm for 30 s, followed by annealing at 120 °C for 10 min. Perovskite solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Annealing was then carried out at 120 °C for 10 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, followed by annealing at 100 °C for 5 min.

[0049] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0050] Comparative Example 2 A perovskite solar cell is fabricated as follows: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0051] Precursor solution preparation: Add 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI2 to 0.9 mL of a mixed dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solution (745 μL DMF + 155 μL DMSO). Then add 15 mg MACl and 35 mg PbI2 to improve the quality of the perovskite film. Add PIL (1 mg / mL) and stir to form a homogeneous solution.

[0052] Spin-coating: SAM in ethanol solution was spin-coated onto FTO at 3000 rpm for 30 s, followed by annealing at 120 °C for 10 min. Perovskite solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Annealing was then carried out at 120 °C for 10 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, followed by annealing at 100 °C for 5 min.

[0053] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0054] Comparative Example 3 A perovskite solar cell is fabricated as follows: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0055] Precursor solution preparation: Add 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI2 to 0.9 mL of a mixed dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solution (745 μL DMF + 155 μL DMSO). Then add 15 mg MACl and 35 mg PbI2 to improve the quality of the perovskite film. Add 1 L (0.5 mg / mL) and stir to form a homogeneous solution.

[0056] Spin-coating: SAM in ethanol solution was spin-coated onto FTO at 3000 rpm for 30 s, followed by annealing at 120 °C for 10 min. Perovskite solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Annealing was then carried out at 120 °C for 10 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, followed by annealing at 100 °C for 5 min.

[0057] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0058] The electrochemical performance of the perovskite solar cells prepared in Examples 1-3 and Comparative Examples 1-3 was tested, such as... Figure 2-7 As shown. Comparative Example 1 corresponds to Figure 2 The JV curve for the perovskite solar cell device without additive engineering optimization shows a cell efficiency of 24.37%; Comparative Example 2 corresponds to... Figure 3 The JV curve of the perovskite solar cell device optimized with polyionic liquid additives shows a cell efficiency of 25.62%; Comparative Example 3 corresponds to... Figure 4 The JV curve of the perovskite solar cell device optimized with ionic liquid additives shows a cell efficiency of 24.55%. Example 1 corresponds to... Figure 5 The JV curve of the perovskite solar cell device optimized by polyionic liquid additive 1 and ionic liquid additive shows a cell efficiency of 25.98%; Example 2 corresponds to... Figure 6 The JV curve of the perovskite solar cell device optimized by the co-optimization of polyionic liquid additive 2 and ionic liquid additive shows a cell efficiency of 25.78%; Example 3 corresponds to... Figure 7 The JV curve of the perovskite solar cell device optimized by polyionic liquid additive 3 and ionic liquid additive shows an efficiency of 25.92%. The passivation of lattice defects in the active layer by the polyionic liquid enables effective carrier separation, corresponding to an increase in current density in electrochemical performance. The ionic liquid mainly acts on the passivation of ionic defects in the active layer, corresponding to an increase in open-circuit voltage in electrochemical performance. Time-of-flight second-time-of-flight second-time ion mass spectrometry was performed on the active layer synergistically regulated by the polyionic liquid and ionic liquid additive. Figure 8As shown, the polyionic liquid and ionic liquid additives achieve a two-component spatial synergistic design, with the polyionic liquid anchoring the active layer surface and the ionic liquid flowing and filling to achieve spatial complementarity. Furthermore, the defect passivation effect was characterized by spatially confined current testing. The device structure is FTO / SAMs / PVK / MoO3 / Ag, and the test results are shown below. Figure 9 As shown, the defect state density of the device was significantly improved by the synergistic effect of polyionic liquid and ionic liquid, and the effect was better than that of either effect alone. The device was subjected to nitrogen atmosphere storage stability tests, as shown... Figure 10 As shown, polyionic liquids and ionic liquids achieve multidimensional synergistic effects, simultaneously passivating lattice defects and ionic defects, resulting in a significant improvement in photoelectric conversion efficiency and stability.

[0059] Example 4 A perovskite solar cell synergistically modified with polyionic liquid and ionic liquid, with the structure as follows: Figure 1 As shown, the structure of this battery includes: a glass substrate, a bottom electrode layer (FTO conductive glass), a hole transport layer (hybrid SAMs), and a perovskite absorber layer (Cs). 0.05 MA 0.1 FA 0.85 PbI3), electron transport layer (C60, BCP), top electrode layer (silver electrode).

[0060] The perovskite solar cell is prepared as follows: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0061] Preparation of perovskite precursor solution: 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI₂ were added to 0.9 mL of a mixed solution of dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) (745 μL DMF + 155 μL DMSO). Then, 15 mg MACl and 35 mg PbI₂ were added to improve the quality of the perovskite film. PIL-1 (P[bvim]Cl) (0.1 mg / mL) and IL ([bmin]SCN) (0.1 mg / mL) were added, and the mixture was stirred to form a homogeneous solution.

[0062] Spin-coating: The mixed SAMs solution was spin-coated onto FTO at 3000 rpm for 30 s, and then annealed at 120 °C for 10 min. The perovskite precursor solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Then, it was annealed at 250 °C for 5 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, and then annealed at 100 °C for 5 min.

[0063] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0064] Example 5 A perovskite solar cell synergistically modified with polyionic liquid and ionic liquid, with the structure as follows: Figure 1 As shown, the structure of this battery includes: a glass substrate, a bottom electrode layer (FTO conductive glass), a hole transport layer (hybrid SAMs), and a perovskite absorber layer (Cs). 0.05 MA 0.1 FA 0.85 PbI3), electron transport layer (C60, BCP), top electrode layer (silver electrode).

[0065] The perovskite solar cell is prepared as follows: Preparation of mixed SAMs solution: Hole transport layer (HTL) was prepared in a glove box using a mixed SAM solution of 2PACz and Me-4PACz. The concentration of 2PACz was 0.17 mg / ml, the concentration of Me-4PACz was 0.33 mg / ml, and the solvent was ethanol.

[0066] Preparation of perovskite precursor solution: Add 0.075 mmol CsI, 0.15 mmol MAI, 1.275 mmol FAI, and 1.5 mmol PbI2 to 0.9 mL of a mixed dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) solution (745 μL DMF + 155 μL DMSO). Then add 15 mg MACl and 35 mg PbI2 to improve the quality of the perovskite film. Add PIL-1 (P[bvim]Cl) (concentration 10 mg / mL) and IL ([bmin]SCN) (concentration 10 mg / mL) and stir to form a homogeneous solution.

[0067] Spin-coating: The mixed SAMs solution was spin-coated onto FTO at 3000 rpm for 30 s, and then annealed at 120 °C for 10 min. The perovskite precursor solution was spin-coated at 1000 rpm for 10 s (acceleration rate 500 rpm) and at 5000 rpm for 35 s (acceleration rate 1000 rpm), respectively. In the last 15 s of the second step, 150 μL of anisole was added as an antisolvent. Then, it was annealed at 50 °C for 60 min. 18 mM 3MTPAI was dissolved in 1 mL of isopropanol / chlorobenzene (1:1 v / v) solvent, filtered, and used. 120 μL of the mixed solution was spin-coated onto the perovskite absorber layer at 4000 rpm for 25 s, and then annealed at 100 °C for 5 min.

[0068] Coating: Evaporation deposition of 27nm C60, 7nm BCP, and 100nm Ag.

[0069] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing a perovskite absorber layer, characterized in that, A perovskite precursor solution was prepared by dispersing and dissolving a perovskite precursor, a polyionic liquid, and an ionic liquid in an organic solvent; the perovskite precursor solution was then spin-coated into a film, and after annealing, a perovskite absorber layer was obtained.

2. The method for preparing the perovskite absorber layer according to claim 1, characterized in that, The perovskite precursor is a raw material for forming the ABX3 perovskite structure, wherein A is an organic cation and / or a Group 1 metal cation; B is one or more of Pb, Sn, Bi, Cu and Ag; and X is one or more of Cl, Br and I.

3. The method for preparing the perovskite absorber layer according to claim 2, characterized in that, The perovskite precursors are CsI, MAI, FAI, PbI2, SnI2, MACl, and MABr.

4. The method for preparing the perovskite absorber layer according to any one of claims 1-3, characterized in that, The general structural formula of the polyionic liquid is [R1R2A]. + -R3] n [X - ] n Where R1 and R2 are independently selected from C1-C 18 Alkyl, alkenyl, aryl, or polymeric chain; R3 is H or C1-C5 alkyl; X- is selected from Cl - ,Br - I - [BF4] - [PF5] - [SCN] - [Tf2N] - Or [CH3COO] - A represents imidazole or pyridine; the degree of polymerization n is 5-1000.

5. The method for preparing the perovskite absorber layer according to claim 4, characterized in that, The general formula of the ionic liquid structure is [R1R2A]. + -R3][X - ], where R1 and R2 are independently selected from C1-C 18 Alkyl, alkenyl, aryl, or polymeric chain; R3 is H or C1-C5 alkyl; X- is selected from Cl - ,Br - I - [BF4] - [PF5] - [SCN] - [Tf2N] - Or [CH3COO] - A represents imidazole or pyridine.

6. The method for preparing the perovskite absorber layer according to claim 1, characterized in that, The organic solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, γ-butyrolactone, 2-methoxyethanol, and methyl acetate.

7. The method for preparing the perovskite absorber layer according to claim 6, characterized in that, The concentration of the polyionic liquid in the perovskite precursor solution is 0.1-10 mg / ml, and the concentration of the ionic liquid is 0.1-10 mg / ml.

8. The method for preparing the perovskite absorber layer according to claim 7, characterized in that, The annealing temperature is 50-250℃, and the time is 5-60 minutes.

9. The perovskite absorber layer prepared by the method according to any one of claims 1-8.

10. A polyionic liquid-ionic liquid synergistically modified perovskite layer solar cell, taking a single-junction perovskite solar cell as an example, its structure from bottom to top consists of a bottom electrode layer, a hole transport layer / electron transport layer, a perovskite absorber layer, an electron transport layer / hole transport layer, and a top electrode layer, characterized in that, The perovskite absorber layer is the perovskite absorber layer as described in claim 9.

Citation Information

Patent Citations

  • Method of improving perovskite solar cell efficiency by using ionic liquid additive

    CN106816535A

  • Method for improving air stability of trans all-inorganic perovskite solar cell based on ionic liquid

    CN114242902A

Cited By

  • Three-junction composite laminated solar cell and manufacturing method thereof

    CN122161170A

  • A triple-junction compound stack solar cell and a manufacturing method thereof

    CN122161170B